Two new species of the genus Sphingonotus Fieber, 1852 (Orthoptera: Oedipodidae) from China - Cao, Cheng-Quan; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2016)
Two new species of the genus Sphingonotus Fieber, 1852, namely Sphingonotus taiwanensis sp. nov. and Sphingonotus zhongningensis sp. nov. are described in this paper from China. The new species Sphingonotus taiwanensis sp. nov. is similar to Sphingonotus nebulosus (Fiescher-Waldheim, 1846), but differs from the latter by interspace of mesosternum wider, width 1.8 times the length; hind femur pale red on inner side; hind tibia pale red, with 13 spines on inner side and 10 spines on outer side; hind wing pale yellow at base. The new species Sphingonotus zhongningensis sp. nov. is similar to Sphingonotus salinus (Pallas, 1773), but differs from the latter in: vertical diameter of eye 1.3 times horizontal diameter; metazona of pronotum is 2.0 times prozona in length; hind tibiae with 13 spines on inner side and 12 spines on outer side; black band of hind wing wider in the middle, apical part not narrowed; black band of hind wing in the apical part larger, not divided into two.        The type specimens are deposited in the Taiwan Agricultural Research of Institute (TARI), Taichung Taiwan, China and in the College of Plant Protection, China Agricultural University, Beijing, China respectively.